ANALISIS KORELASI PEARSON DALAM MENENTUKAN HUBUNGAN ANTARA PDRB JAWA TENGAH DENGAN ARUS PETIKEMAS TPK SEMARANG - Arif, An Zaenal; Muldiyono, Rachmat; Sulistyo, Juny Andry (Jurnal Teknik Sipil Giratory UPGRIS, 2026)
This study aims to analyze the correlation between the Gross Regional Domestic Product (GRDP) of Central Java Province and container throughput at the Semarang Container Terminal. Using time series data from 2015 to 2024, a Pearson correlation analysis was conducted to measure the strength of the relationship between the two variables. The results indicate a very strong and positive correlation between Central Java’s GRDP and container throughput, suggesting that regional economic growth is closely linked to the expansion of logistics and port activities. These findings are significant as a basis for policy formulation in developing port infrastructure that aligns with regional economic growth.